The Mediating Role of Parent-Child Attachment in The Relationship between Parenting Stress and Social-Emotional Development among Dual-Career Families in Indonesia - Shafa Alistiana Irbathy; Khusnul Amalin; Azim Abdurakhmovich Yuldashev (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
This study examined the mediating role of parent-child attachment in the relationship between parenting stress and early childhood social-emotional development among dual-career families in Indonesia. The phenomenon of dual-career families has increased rapidly, with more than 70% of Indonesian families having both parents working. Time constraints and job demands often lead to parenting stress, which may compromise the quality of parent-child interaction and attachment. Despite extensive research on these variables separately, limited studies have integrated them into a comprehensive mediation model, particularly in non-Western contexts. This study employed a sequential explanatory mixed-method design. A quantitative survey involved 250 dual-career parents with children aged 3-6 years from SD Muhammadiyah Tonggalan Klaten and SD IT Al Furqoon Klaten, followed by in-depth interviews with 20 participants. Instruments included the Parenting Stress Index (PSI), Attachment Style Questionnaire (ASQ), and Devereux Early Childhood Assessment (DECA). Results showed that 68% of dual-career parents experienced moderate to high parenting stress. Parenting stress was significantly negatively correlated with secure parent-child attachment (r = -0.52, p < 0.01) and children's social-emotional development (r = -0.48, p < 0.01). Mediation analysis revealed that parent-child attachment partially mediated this relationship (indirect effect = -0.23, 95% CI [-0.31, -0.15]), with 46% of the total effect occurring through reduced attachment quality. Qualitative findings supported these results, demonstrating that parental exhaustion led to reduced responsiveness and insecure attachment. These findings contribute to attachment theory by empirically demonstrating the mediation mechanism in a non-Western context. Implications include the need for family-based interventions and family-friendly school policies.